2015
DOI: 10.1109/tsc.2014.2355842
|View full text |Cite
|
Sign up to set email alerts
|

Unified Collaborative and Content-Based Web Service Recommendation

Abstract: The last decade has witnessed a tremendous growth of Web services as a major technology for sharing data, computing resources, and programs on the Web. With increasing adoption and presence of Web services, designing novel approaches for efficient and effective Web service recommendation has become of paramount importance. Most existing Web service discovery and recommendation approaches focus on either perishing UDDI registries, or keyword-dominant Web service search engines, which possess many limitations su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(99 citation statements)
references
References 43 publications
1
97
0
1
Order By: Relevance
“…Approaches on time‐aware service recommendation can be categorized depending on the target recommendation time. We distinguish continuous time‐aware approaches, categorical time‐aware approaches, and time‐adaptive approaches . These three categories are described in the following sections.…”
Section: Time Information In Service Recommendationmentioning
confidence: 99%
“…Approaches on time‐aware service recommendation can be categorized depending on the target recommendation time. We distinguish continuous time‐aware approaches, categorical time‐aware approaches, and time‐adaptive approaches . These three categories are described in the following sections.…”
Section: Time Information In Service Recommendationmentioning
confidence: 99%
“…However, this approach performs poorly if the user group size is small or the historical rating data are sparse, which is the well-known cold start problem. Recent studies [25][26][27][28] have demonstrated that a hybrid approach, combining CF and content-based approaches can provide more accurate recommendations and solve some of the common problems in recommendation systems such as cold start and the sparsity problem. Even so, it does not perform recommendation based on spatial data.…”
Section: General Recommendation Systemmentioning
confidence: 99%
“…H. H. Ngu, Jian Yu, and Aviv Segev (2014), Presented Unified Collaborative and Content-Based Web Service Recommendation [10]. The author proposes a novel hybrid approach that consolidates collaborative filtering and semantic content-based methods for a recommendation of services.…”
Section: Review Of Literaturementioning
confidence: 99%